Evidence of Magnetoacoustic Oscillations above the Brightened and Magnetically Active Quiet-Sun - Srivastava A.K.; Dwivedi B.N. (My University, 2025)
We study the near photospheric Fe I 6302 Å (V-component) and chromospheric Ca II H 3968 Å radiance oscillations in the lower solar atmosphere above the four brightened and magnetically active regions of the quiet-Sun as observed by the solar optical telescope onboard Hinode. At the chosen locations (L1, L3, L4), we obtain the statistically significant periods of 5.0 min both in Ca II H and Fe I fluxes, which is interpreted as the likely signature of the presence of 5.0 min magnetoacoustic oscillations. It is also found that the higher period (7.0 min) of magnetoacoustic waves, as observed at another location (L2), may be generated locally in the quiet-Sun tube and leak to higher heights. We suggest that 5.0 min global acoustic oscillations are converted into magnetoacoustic one in the strongly magnetized quiet-Sun fluxtubes. Noting that the magnetoacoustic waves in strongly magnetized regions can transfer energy twice compared to the acoustic waves in the non-magnetized regions, the directly observed these 5.0 min magnetoacoustic oscillations at photospheric and chromospheric heights above the strongly magnetized regions reveal the transfer of significant amount of energy to partially balance the localized energy losses. © 2017, Indian Academy of Sciences.